Study on Functional Oligosaccharides Technical Aspects, Properties, Applications, Regulations, and Health Benefits - O. Ibrahim, Osama (Emerging Challenges in Agriculture and Food Science Vol. 3, 2022)
Functional oligosaccharides are carbohydrates that have two to ten monosaccharides units linked together by glycosidic bonds. Maltose, sucrose, and lactose are disaccharides of two monosaccharides also linked together by glycosidic bonds. These three disaccharides are digestible sugars by gut enzymes and are not classified as functional oligosaccharides. Functional oligosaccharides are mostly non-digestible by gut enzymes and provide health benefits as fibers and prebiotics [1]. The commonly known functional oligosaccharides are fructo-oligosaccharides, galacto-oligosaccharides, lacto-sucrose, malto-oligosaccharides, isomalto-oligosaccharides, trehalose, cyclodextrins, xylo-oligosaccharides, and soy-oligosaccharides. The objective from this study is to highlight the beneficial physiologic functions of these functional oligosaccharides for humans and animals’ health. Functional oligosaccharides have mildly sweet taste and other characteristics such as, mouth feeling. This mouth feeling characteristic interest food industry to incorporate these functional oligosaccharides in foods as a partial substitute to fat and sugars, plus to improve food texture. With the exception, of malto-oligosaccharides and trehalose, functional oligosaccharides are non-digestible in small intestine by gut digestive enzymes and reach large intestine (colon) where it acts as a growth factor (prebiotics) to enhance the growth of beneficial bacteria (probiotics) and to inhibit the growth of pathogenic bacteria via competitive exclusion system. These benefits to colon and other health benefits in addition to the unique chemical and physical characteristics of function oligosaccharides increased their global market applications in foods, pharmaceuticals, and in other industries. In addition, two of these functional oligosaccharides, cyclodextrins and trehalose have an important pharmaceutical application in drugs delivery system, and as cryoprotectants for biological materials, viable cells, and also for foods. Due to, the increase demand of functional oligosaccharides for their health benefits and for other characteristics, functional oligosaccharides are currently produced enzymatically at higher yield, and lower cost from different natural sources of carbohydrates as a replacement to costly plants extraction methods.